Kritisk empiri. Ett historiografiskt perspektiv - Caldenby, Claes (Nordlit, 2015)
The article discusses the possible value of a ”critical empiricism” as the forgotten ”other” of the well-established critical theory. Following Swedish sociologist Johan Asplund, critical empiricism is described as ”seeing what others have not seen”. The ”theoretical turn” in architectural research is questioned with the help of architectural historians Anders Åman and Mari Hvattum. The 1940s discussion of Swedish architecture as “new empiricism” introduces a strong relation between the Nordic welfare societies and their architecture as a characteristic also of Swedish architectural history. The article presents a recent historiographical project by a network of Swedish architectural historians from universities and schools of architecture. One of the networks’ papers is about Gregor Paulsson’s book Svensk stad [Swedish Town], an “environmental history” with a pronounced sociological perspective and an ambition to influence Swedish post-war planning. Another paper discusses architectural history as the study of building categories, a firmly established tradition in Swedish architectural history, in this case with a fundamentally “functional” perspective. A third paper is a critical study of the 1970s turn from architectural history as a history of monuments to a history of the built environment in its broadest sense. In conclusion, critical empiricism in architectural history is presented as a vigorous and necessary reminder of how society could be different in a time when humanities as well as planning are questioned by politicians.